Nanotechnology applications for clean water solutions for improving water quality - Street, Anita; Duncan, Jeremiah; Sustich, Richard; Savage, Nora (Amsterdam William Andrew, 2014)
Nanotechnology is already having a dramatic impact on improving water quality and the second edition of Nanotechnology Applications for Clean Water highlights both the challenges and the opportunities for nanotechnology to positively influence this area of environmental protection. This book presents detailed information on cutting-edge technologies, current research, and trends that may impact the success and uptake of the applications. Recent advances show that many of the current problems with water quality can be addressed using nanosorbents, nanocatalysts, bioactive nanoparticles, nanostructured catalytic membranes, and nanoparticle enhanced filtration. The book describes these technologies in detail and demonstrates how they can provide clean drinking water in both large scale water treatment plants and in point-of-use systems. In addition, the book addresses the societal factors that may affect widespread acceptance of the applications. Sections are also featured on carbon nanotube arrays and graphene-based sensors for contaminant sensing, nanostructured membranes for water purification, and multifunctional materials in carbon microspheres for the remediation of chlorinated hydrocarbons.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Water-supply engineering -- Technological innovations; Water -- Purification -- Technological innovations; Water -- Pollution -- Prevention; Nanotechnology; Nanostructured materials; Electronic books